Ischemic preconditioning and tacrolimus pretreatment as strategies to attenuate intestinal ischemia-reperfusion injury in mice - Stringa, Pablo Luis (2013)
The intestine is highly sensitive to ischemia-reperfusion injury (IRI), a phenomenon occurring in different intestinal diseases. Several strategies to mitigate IRI are in experimental stages; unfortunately, no consensus has been reached about the most appropriate one. We report a protocol to study ischemic preconditioning (IPC) evaluation in mice and to combine IPC and tacrolimus (TAC) pretreatment in a warm ischemia model. Mice were divided into treated (IPC, TAC, and IPC þ TAC) and untreated groups before intestinal ischemia. IPC, TAC, and IPC þ TAC groups were able to decrease postreperfusion nitrites levels (P < .05). IPC-containing groups had a major beneficial effect by preserving the integrity of the intestinal histology (P < .05) and improving animal survival (P < .002) compared with TAC alone or the untreated group. The IPC þ TAC group was the only one that showed significant improvement in lung histological analysis (P < .05). The TAC and IPC þ TAC groups down-regulated intestinal expression of interleukin (II)-6 and IL1b more than 10-fold compared with the control group. Although IPC and TAC alone reduced intestinal IRI, the used of a combined therapy produced the most significant results in all the local and distant evaluated parameters.